FAMILY READING IS THE FOUNDATION OF SPIRITUAL WELL-BEING - Dusyorova Klara Narmuminovna (Bright Mind Publishing, 2025)
If we look at the development and progress of society and the nation, the role of educated, spiritual and enlightened youth in the development of society is incomparable. One of the main factors that perfectly educate such youth is the book as a means of reading. The most unique discovery created by mankind that lifts us from the earth to the sky, leads us to perfection, brings light and warmth into the hearts of people, helps us to consciously understand the difference between black and white, good and evil, destructive and creative is the book. The book glorifies man, cultivates human virtues such as loving the homeland, humanity, looking at the life one lives with a sense of gratitude, being kind and polite to others, and sharing goodness with people around. The importance of books in human life is immeasurable. They are an unfailing guide that illuminates the path of human life, a source of happiness that gives meaning to human life, and a loyal friend who accompanies us in any situation.
Keywords: Interest in books, reading culture, spiritual perfection, succesfull, educated youth, family environment, family values, spiritual degree.